Nevrogena motnja delovanja sečil - Moharić, Metka (Rehabilitacija (Ljubljana), 2023)
Lower urinary tract dysfunction is a common sequel of neurological disease resulting in symptoms that significantly impact quality of life. The site of the neurological lesion and its nature influence the pattern of dysfunction. The risk for developing upper urinary tract damage and renal failure is considerably lower in patients with slowly progressive non-traumatic neurological disorders, compared to those with spinal cord injury or spina bifida. This acknowledged difference in morbidity is considered when developing appropriate patient-management algorithms. The preliminary evaluation consists of history taking and bladder diary, and may be supplemented by tests such as uroflowmetry, post-void residual measurement, renal ultrasound, (video)urodynamics, neurophysiology and urethrocystoscopy, depending on the clinical indications. Incomplete bladder emptying is most often managed by intermittent catheterisation, and storage dysfunction is managed by antimuscarinic medications. Intra-detrusor injections of botulinum toxin A have greatly facilitated the management of neurogenic detrusor overactivity. Neuromodulation offers promise for managing both storage and voiding dysfunction. In selected patients, reconstructive urological surgery may become necessary. An individualised, patient-tailored approach is required for the management of lower urinary tract dysfunction in this special population.
Keywords: incontinence; nehotno uhajanje seča; neurogenic bladder; neurological impairment; nevrogeni mehur; nevrološke okvare; postvoid residual; rehabilitation; treatment; Urologic Diseases; zaostajanje po uriniranju; zdravljenje